Evidence of (in)applicability of Morphological Doubling Theory in Acehnese reduplication - Faisal Mustafa (EduLite: Journal of English Education, Literature and Culture, 2022)
Morphological Doubling Theory (MDT) states that reduplication is a process in morphology, instead of phonology, which calls the second element as a reduplicant to add meaning to the base. This research is to investigate to what extent MDT is applicable to analyze reduplications in Acehnese, an Austronesian language spoken in Indonesia. The research was based on nine literary works called hikayat written in early 20th century or earlier. The number of tokens extracted from the data source is 1076, or 370 tokens after duplicates were removed, consisting of 360 reduplicated words and ten synonym compounds. The data were analyzed using a complete qualitative data analysis procedure consisting of immersion, reflecting, taking apart, recombining, and relating and locating data. The results show that all reduplication patterns in Acehnese – full reduplication, partial reduplication and rhyming reduplication – can be analyzed using MDT. This result suggests that reduplication in Acehnese is a morphological process, where phonology is involved only in shaping the output of the reduplicant. In this language, a stem is called twice by morphology to satisfy the romantic requirements such as to mark plurality and to put emphasize in the base.